Detection of Clostridium perfringens in tsunami deposits after the Great East Japan Earthquake. (30th May 2019) - Makino, Asuka; Xu, Jun; Nishimura, Junko; Isogai, Emiko
Abstract: The Great East Japan Earthquake struck off the Tohoku and caused a tsunami in 2011. Most of the microbial characteristics of tsunami‐affected soil remain unknown and no published study has shown how a tsunami affects the risk of infection by Clostridium perfringens living in soil. In 2011 and 2015, C. perfringens was assessed in deposits in soil from tsunami‐damaged areas and undamaged areas of Miyagi. It was found that the number of C. perfringens was overwhelmingly greater in 2011 than in 2015 in the tsunami‐damaged areas. According to real‐time PCR, the prevalence C. perfringens organisms (%) was 10 3 fold greater in the damaged than in the undamaged areas.